2016
DOI: 10.1371/journal.pone.0161676
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Propionibacterium acnes in Intervertebral Discs of Patients Undergoing Lumbar Microdiscectomy: A Prospective Cross-Sectional Study

Abstract: BackgroundThe relationship between intervertebral disc degeneration and chronic infection by Propionibacterium acnes is controversial with contradictory evidence available in the literature. Previous studies investigating these relationships were under-powered and fraught with methodical differences; moreover, they have not taken into consideration P. acnes’ ability to form biofilms or attempted to quantitate the bioburden with regard to determining bacterial counts/genome equivalents as criteria to differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 29 publications
(55 reference statements)
4
68
1
Order By: Relevance
“…Nearly 84% of these patients were found to have P. acnes [25]. Recently, a significant portion of herniated discs (11%) have been shown to have a high P. acnes bacterial load (> 1000 CFU/mL) [26]. Aghazadeh et al also found a high prevalence of P. acnes DNA and correlated it to vertebral edema as seen on preoperative MRI [27].…”
Section: Propionibacterium Acnesmentioning
confidence: 99%
“…Nearly 84% of these patients were found to have P. acnes [25]. Recently, a significant portion of herniated discs (11%) have been shown to have a high P. acnes bacterial load (> 1000 CFU/mL) [26]. Aghazadeh et al also found a high prevalence of P. acnes DNA and correlated it to vertebral edema as seen on preoperative MRI [27].…”
Section: Propionibacterium Acnesmentioning
confidence: 99%
“…In 11 independent studies published between 2001 and 2016, involving 1188 combined patients undergoing discectomy or microdiscectomy, this Gram-positive bacterial species was isolated from ~25% of resected disc specimens [111]. However, these studies had significant methodical differences and the majority was statistically underpowered [19] Moreover, the use of qualitative microbiologic techniques—i.e.…”
Section: Introductionmentioning
confidence: 99%
“…acnes can be slow to grow and often proliferates in vivo as aggregated biofilms, which can be challenging to cultivate in vitro and require physical biofilm disassembly (e.g. through sonication or homogenization) prior to microbiologic plating [1113]. As a result, standard specimen preparation and culture techniques could lead to false negative results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that the prevalence of low-virulence anaerobic bacterium ranged from 20% to 53% [17]. Among them, P. acnes has been found to account for as much as 84% of all isolated bacteria [7].…”
Section: Introductionmentioning
confidence: 99%